Wireless Algorithms, Systems, and Applications Third International Conference, WASA 2008, Dallas, TX, USA, October 26-28, 2008. Proceedings - Li, Yingshu; Huynh, Dung T.; Das, Sajal K.; Du, Ding-Zhu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the Third Annual International Conference on Wireless Algorithms, Systems, and Applications, WASA 2008, held in Dallas, TX, USA, in October 2008. The 35 revised full papers presented together with 3 keynote talks and 15 invited lectures were carefully reviewed and selected from numerous submissions. Providing a forum for researchers and practitioners, from the academic, industrial and governmental sectors, the papers address current research and development efforts of various issues in the area of algorithms, systems and applications for current and next generation infrastructure and infrastructureless wireless networks.
Research Challenges in Complex Large Scale Networks and Cyber Physical Systems -- China$1 (Bs National Research Project on Wireless Sensor Networks -- A Utility-Based Routing Scheme in Ad Hoc Networks -- Delivery Guarantee of Greedy Routing in Three Dimensional Wireless Networks -- Landmarks Selection Algorithm for Virtual Coordinates Routing -- Energy Efficient Broadcast Routing in Ad Hoc Sensor Networks with Directional Antennas -- DTN Routing with Probabilistic Trajectory Prediction -- A Simple Yet Effective Diversifying Improvement of the Minimum Power Multicast Tree Algorithms in Wireless Ad Hoc Networks -- Analytical Study of the Expected Number of Hops in Wireless Ad Hoc Network -- HoP: Pigeon-Assisted Forwarding in Partitioned Wireless Networks -- Load-Based Metrics and Flooding in Wireless Mesh Networks -- New Approximation for Minimum-Weight Routing Backbone in Wireless Sensor Network -- Ant Colony Optimization-Based Location-Aware Routing for Wireless Sensor Networks -- Multi-path GEM for Routing in Wireless Sensor Networks -- Construction of Minimum Connected Dominating Set in 3-Dimensional Wireless Network -- Maintaining CDS in Mobile Ad Hoc Networks -- PTAS for Minimum Connected Dominating Set in Unit Ball Graph -- A Better Theoretical Bound to Approximate Connected Dominating Set in Unit Disk Graph -- Minimum Power Minimum D-Hop Dominating Sets in Wireless Sensor Networks -- Convex Combination Approximation for the Min-Cost WSN Point Coverage Problem -- p-Percent Coverage in Wireless Sensor Networks -- Prolonging Network Lifetime for Target Coverage in Sensor Networks -- An Environmental Monitoring System with Integrated Wired and Wireless Sensors -- An Energy-Efficient Object Tracking Algorithm in Sensor Networks -- Sensor Deployment for Composite Event Detection in Mobile WSNs -- Reliable and Fast Detection of Gradual Events in Wireless Sensor Networks -- Mobility Model and Relay Management for Disaster Area Wireless Networks -- Relay Nodes in Wireless Sensor Networks -- Transmission Scheduling for CBR Traffic in Multihop Wireless Networks -- Leader Election Algorithms for Multi-channel Wireless Networks -- Clock Offset Estimation in Wireless Sensor Networks Using Bootstrap Bias Correction -- Correlation Analysis for Spreading Codewords in Quasi-synchronous CDMA Communication -- Energy Consumption Reduction of a WSN Node Using 4-bit ADPCM -- Minimizing Transferred Data for Code Update on Wireless Sensor Network -- Opportunistic Cooperation with Receiver-Based Ratio Combining Strategy -- Message-Driven Frequency Hopping $1 (BDesign and Analysis -- Toward a Real and Remote Wireless Sensor Network Testbed -- An Optimal Algorithm for Minimizing Cluster Overlap of ACE -- Supporting IPv6 Interaction with Wireless Sensor Networks Using NP++ -- The Effect of Re-sampling on Incremental Nelder-Mead Simplex Algorithm: Distributed Regression in Wireless Sensor Networks -- C-kNN Query Processing in Object Tracking Sensor Networks -- Power-Efficient Data Exchanging Algorithm in Wireless Mesh Networks -- Composite Spatio-Temporal Co-occurrence Pattern Mining -- Belief Propagation in Wireless Sensor Networks - A Practical Approach -- A Random Key Management Scheme for Wireless Sensor Networks -- WORMEROS: A New Framework for Defending against Wormhole Attacks on Wireless Ad Hoc Networks -- Designing Secure Protocols for Wireless Sensor Networks -- Privacy-Preserving Communication Algorithms and Network Protocols -- Secure Multi-party Protocols for Privacy Preserving Data Mining -- Enhancing Software Product Line Maintenance with Source Code Mining -- Software Fault Localization Using N-gram Analysis -- Recyclable Connected Dominating Set for Large Scale Dynamic Wireless Networks -- Locate More Sensors with Fewer Anchors in Wireless Sensor Networks.s
Keywords: Computer science; Computer communication systems; Computer system failures; Computer programming; Computers; Algorithms; Computer Science; Programming Techniques; Computer Communication Networks; Theory of Computation; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Electronic books